DAMPAK KRISIS TERHADAP PERMINTAAN UANG DI INDONESIA PERIODE 1994-2004 - Darmansyah Darmansyah (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2005)
The paper examines relationship of the demand for money in Indonesia with national income (GDP real), interest rate (time deposit interest rate (quarterly)), inflation rate (the growth ofCPI) and crisis (dummy, which 0 = before crisis (from 1994:1 to 1997:2) and 1 = crisis (from 1997:3 to 2004:4) and to determine which variable had the most dominant effect to demand for money and also to know the demand for money stability in Indonesia in 1994-2004 period. To know the effect of the independent variables to the dependent variable we using regression models with OLS (Ordinary Least Squares) method and to know the stability we using the dummy variable approach. The result of the regression show GDP real, interest rate, inflation and crisis had effect to demand for money Ml and M2, and the stability test find there is instability demand for money Ml andM.2 in Indonesia.